Referral to rehabilitation in Parkinson's disease: who, when and to what end? - Josefa Domingos; Miguel Coelho; Joaquim J Ferreira (Arquivos de Neuro-Psiquiatria)
The current state of evidence in non-pharmacological treatments amounts to an impending paradigm shift in neurology where physicians should be alerted that some rehabilitation interventions are already supported in current therapeutic guidelines. This manuscript aims to overview the best scientific data supporting referral to rehabilitation services in order to help physicians make the best use of the existing evidence for non-pharmacological treatments in the different stages of Parkinson´s disease.